Mineral nutrients and heavy metal evaluation and their relationship with morpho-agronomic traits in new rice varieties with qDTYs and Sub1 QTL - Mohd Ikmal, Asmuni; Abd Razak, Siti Nurfaeiza; Sulaiman, Nadzrie; Yahya, Ahmad Shukry; Zulkifli, Nadiatur Akmar (National Information and Documentation Centre, 2025)
Malaysia has released over 55 rice varieties, but none are high in mineral nutrients, especially zinc and iron. Furthermore, some rice varieties with high nutrient content and high yields can be contaminated with heavy metals such as arsenic and cadmium. This study examined the concentration of mineral nutrients and heavy metals in polished and unpolished rice with morpho-agronomic traits and with qDTYs and Sub1 in the genotypes. Five genotypes viz. UKM5, UKM112, UKM37, UKM54, and UKMRC9 were field-tested using a completely randomised design with four replications. After one planting season, morpho-agronomic data was collected. The harvested grain was processed and analysed for mineral nutrients and heavy metal content. In this study, unpolished rice has more Zn, Fe, and As, while polished rice has more Cd. UKM112 rice has the best morpho-agronomic traits, high mineral nutrient content, and low metal content, especially after being polished. The combination of qDTY3.1 and Sub1 increased morpho-agronomic traits, mineral nutrients, and heavy metals, while qDTY12.1 and qDTY3.1 had the opposite effect. This study also found that while mineral nutrients boost grain yield and plant growth, heavy metals may also accumulate under specific conditions. This study can have a significant impact on the problems of malnutrition and rice income faced in Malaysia. The selected rice genotype can also be used as a donor parent to produce more rice varieties that are high in mineral nutrients, low in heavy metals, and high-yielding for Malaysia.